Integration of Islamic Values and Modernization in Sasak Wedding Traditions in Lombok - Kurnia Pratama, M Maulana; Mustari, Mustari; Karim, Abdul (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
This research aims to explore the dynamics of change and continuity in the wedding traditions of the Sasak community in Lombok from an Islamic perspective and its impact on their social structure. The Sasak community possesses a rich cultural heritage passed down through generations, with wedding traditions being one of the essential foundations of their social life. This study employs Lévi-Strauss's structuralism approach to delineate the key elements in Sasak wedding ceremonies and analyze the role and symbolic meaning of each element in the context of Islamic teachings. Sasak wedding traditions reflect traditional values highly esteemed by the community, such as togetherness, mutual cooperation, and respect for ancestors. The influence of Islam, which has permeated Sasak life, creates a unique cultural synthesis where traditional elements are integrated with Islamic practices. However, modernization and globalization bring significant changes to the wedding traditions and social structure of the Sasak community. This research finds that despite strong external influences, the Sasak community has managed to preserve key traditional elements and uphold their traditional values. Through this study, a deep understanding is gained of how the Sasak community faces social changes without losing their cultural and Islamic identity. This research also elucidates how social structure and wedding traditions function as reflections and mechanisms to face contemporary challenges, contributing to structural anthropology studies and providing a broader understanding of socio-cultural dynamics in Indonesia.